The 'nuts and bolts' of including service users and carers in the recruitment of health and social work students in an English university—An interdisciplinary critique. (28th September 2020) - Unwin, Peter; Rooney, Joy
Abstract: Background: The literature regarding inclusion of service users and carers (SUACs) in the recruitment processes for future health and social work professionals has primarily presented such inclusion as positive for all. This study is novel in its exploration of the detail of SUACs' involvement and in its reach across a whole university department of health and social care disciplines. Objective: To examine the detail of ways in which SUACs were actually involved in student selection and whether they have any real influence on recruitment decisions. Method: This co‐produced study took place in an English university. A qualitative, semi‐structured interviewing approach was undertaken with 12 staff across social work, nursing, occupational therapy, physiotherapy, paramedicine and physician associate disciplines. Thematic analysis was employed independently with both researchers agreeing resultant themes. Findings: A range of recruitment activities which included SUACs were found, evidencing both full and partial involvement in decision making. Nine themes emerged—The quality of SUACs' inclusion; Understanding reasons for including SUACs; SUACs being more knowledgeable than academic staff; SUACs influencing final decisions; The high expectations of candidates by SUACs; SUACs' need for training; Marketization and scepticism; and Logistics and the presumption of ableism. Conclusions: Transparent protocols are essential if SUACs are to be equitably included in student recruitment processes. A shared model of SUACs' inclusion should be attainable across disciplines, even if the 'nuts and bolts' of recruitment processes vary. Patient or Public Contribution: This work was co‐produced with a SUACs' group from conception and design through to fieldwork and write‐up.